PENGARUH BUDAYA ORGANISASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN CV. JAPO INDONESIA CIPUTAT TANGERANG SELATAN - Putri Friska Secaria; Ana Septia Rahman (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to determine the effect of organizational culture and competence on employee performance at CV. Japo Indonesia, Ciputat, South Tangerang. This research uses a quantitative method with a population consisting of all 65 employees of CV. Japo Indonesia and applies a saturated sampling technique. The data analysis methods used include validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, simple linear regression, multiple linear regression, correlation coefficient analysis (r), coefficient of determination analysis (R²), and hypothesis testing (t-test and F-test). The results of the t-test show that organizational culture (X₁) has a tcount value of 24.501 > ttable 1.998 with a significance value of 0.001 < 0.05, indicating that organizational culture has a significant effect on employee performance (Y). Competence (X₂) has a tcount value of 31.451 > ttable 1.998 with a significance value of 0.001 < 0.05, meaning that competence also has a significant effect on employee performance. Meanwhile, the simultaneous F-test result shows Fcount 523.209 > Ftable 3.115 with a significance value of 0.001 < 0.05, indicating that organizational culture and competence together have a significant effect on employee performance. The coefficient of determination (R²) is 0.944 or 94.4%, which means that organizational culture and competence contribute 94.4% to variations in employee performance, while the remaining 5.6% is influenced by other factors outside this study.